Steadfast Movement around Micronesia : Satowan Enlargements beyond Migration. - Bautista, Lola Quan, 1968- (Rowman & Littlefield Pub. Group, 2010)
Steadfast Movement examines how people from Chuuk State in the Federated States of Micronesia (FSM) move about and their cultural interpretations of movement itself. Special consideration is made of movement on the atoll of Satowan in Chuuk State asintimately associated with clan, lineage, and locality, as well as the influence of a system of local beliefs and attitudes based on combinations of age, marital status, and childbirth. Lola Quan Bautista also investigates the ways in which the current movement of citizens from Chuuk State and others from FSM to Guam fits within larger contexts that.